The Effect of Pulley Variation on the Power Output of a Three-Bladed Savonius-Type Vertical Axis Wind Turbine - Ihat Solihat; Dimas Abimanyu (Jurnal Teknik dan Science, 2026)
This study aims to analyze the effect of pulley diameter variation on the performance of a three-bladed Savonius-type vertical axis wind turbine. Three pulley diameter variations were used, namely 3 inch, 5 inch, and 8 inch, with testing conducted at wind speeds ranging from 3 to 4.5 m/s. The performance parameters measured included rotational speed (RPM), current, voltage, electrical power output, and torque. The results indicate that the 3-inch pulley configuration provides the best overall performance, producing an average power output of 31.01 W, a rotational speed of 145.53 RPM, and a torque of 12.60 Nm. The 5-inch pulley generated an average power output of 29.14 W with a torque of 10.25 Nm, while the 8-inch pulley produced the lowest average power output of 21.56 W and a torque of 9.4 Nm. The decline in performance observed with larger pulley diameters is attributed to increased rotational load and higher wind speed requirements. Therefore, smaller pulley diameters are more suitable for low wind speed conditions, as they enable more efficient power generation. This study provides a useful reference for the development of small-scale wind turbine designs for renewable energy applications.